PERLINDUNGAN HUKUM BAGI LESSOR PADA PERJANJIAN LEASING (Studi Kasus pada PT.ACC Cabang Semarang) - Djoko Setyo Hartono (JURNAL LITBANG, 2007)
Currently the business envirorunent is very competitive. The businessman has to looking.fbr an e.ffective .funding to support operational and expansion polictt. The alternative funding exception bank is other choice, because the rate commonly is very high and application credit process is not.flexible.Leasing is the one o.f alternatirte /imding, but until todalt espect legal is not suitable. These leasing contact between two pqrties are lessor and lessee. It is possible happened to be that one of the parties not.ful/ill these leasing contract.This research used to yuridis empiris method and research specification using analysis descriptive. The object of research is PT.ACC Finance Semarang branch.Conclusion Jind that legal protection .for lessor based on Article 6 ayat (l),Article 7 ayat (3), Article t huruf (cl), (/), dan (h) Keputusan Menkeu RINo.l169/KMK.01/1991. Beside lhat lessor muking standard contracl which isincluding lessee's responsibility and sanction. Lessor's way to solve the problems are : first of all to give somatie to lessee and./inally way ask to the court, but lessor have to think consider about spending a large of time and money.Key word :leasing contract, lessor, lessee, optie right